Plasma Exchange and Immunoadsorption in Pediatric Inflammatory Optic Neuropathy Resistant to Corticosteroid Therapy: Four French Cases - Jacquet, Coralie; Garnier, Arnaud; Cheuret, Emmanuel (Neuropediatrics, 2016)
Steroids as a foremost therapy are widely used in pediatric optic neuritis (ON). Yet, this treatment is not standardized to date. Some children show a resistance to the classic treatment by steroids. Although plasma exchange (PE) and immunoadsorption (IA) techniques are increasingly being adopted and lead to good results in resistant cases in adult patients, very few studies have shown interest in treating ON when steroids have failed. In this study, we report four observations of children, two of whom are treated by PE and two by IA techniques, describing the treatment protocols together with the side effects observed.
Keywords: optic neuritis; plasma exchange; immunoadsorption; pediatric